External carotid replacement in brain circulatory failure - Palma, Eduardo C.; Rodríguez Martínez, Ricardo; Garbino, Carlos; Peréz Lagrave, Alfredo; Arias, José; Palma, Liliana (Cirugía del Uruguay, 1975)
The externa! carotid artery may become a fundamental route of encephalic circulatory supply, in cases of occlusion of the interna! carotid or vertebral arteries. This may take place through multiple anastomosis between its branches -mainly the occipital arteryand the ones of Willis's circle. In cases of total occlusion of the internal carotid artery, restoration of flow to the external carotid artery by thromboendarterectomy may result in a very important improvement of the encephalic circulation, as it happened in 10 of the 11 cases treated by the authors. If there is a severely symptomatic cerebrovascular insufficiency a transient shunt -from the common carotid arlery to the external carotid artery- is recommended, in order to avoid the severe ischemia resulting from the arterial clamping in these circumstances, which motivated the only unfavourable evolution of the series.